Faktor Penyebab Reviktimisasi di Indonesia: Analisis Terhadap Wanita Korban Kejahatan yang Mengalami Kekerasan Berulang - Rani, Febrina Hertika; Pettanasse, Ismail; Samsul, Samsul; Ikhsan, Rd Muhammad (Legalita, 2024)
Repeat victimisation, also known as revictimisation, is when a person who has been a victim of a crime experiences a similar event at a later date. This phenomenon has become a serious concern in the study of victimology and criminology.To determine and analyse the internal factors that influence women victims of crime so that they are vulnerable to experiencing repeat violence (revictimisation) and explain how patriarchal norms in Indonesian society limit women in reporting or seeking help for self-victimisation in the event that violence is suffered.The type of research applied is normative research.Women are still vulnerable to repeated violence (revictimisation), which is often triggered by several causes, namely extinsic and instrinsic, the internal causes are Women have common characteristics in the form of submission to dominant male power, Women also often experience emotional dependence and attachment / dependence on the perpetrator, fear of the threat of being separated from children, feeling cared for and receiving love and / or because they feel love from their partner, fear of losing it ‘or because they don't have anyone anymore’. In Indonesia, patriarchal norms discourage women from reporting violence and seeking help, which can be exacerbated by stigmatisation and stigma. This situation can be exacerbated by social stigma, powerlessness, economic dependence, reinforcement of adverse power patterns, and cultural norms governing gender roles). Keyword : revictimisation;victim;violence;Patriaki;